1961
DOI: 10.1002/j.1551-8833.1961.tb00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Studies of Turbidity Removal by Coagulation With Aluminum Sulfate

Abstract: One important factor affecting coagulation is the negative zeta potential, often referred to as the charge, that is associated with natural clay particles suspended in water. This article discusses a study of the zeta potential of clay particles that were found to be dependent on the pH and on the alum dosage. An amount of alum equivalent to several times the base‐exchange capacity of the clay suspension was required to neutralize the particle charge. Clarification was best in the range pH 7.5 – 8.5 where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1961
1961
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…According to the method of Schofield and Samson (1954) these fine particles (2 lm) were treated with 0.5 M NaCl or CaCl 2 solution to convert the kaolinite to the sodium form (Na-or Ca-kaolinite). The cation exchange capacity (CEC) of Na-kaolinite was determined by using ammonium acetate (1 M) as described by Black and Hannah (1961). The cation content was determined by atomic absorption spectrophotometer, Shimadzu Corporation, AA-6701/6601 Series.…”
Section: Clay Separation and Saturationmentioning
confidence: 99%
“…According to the method of Schofield and Samson (1954) these fine particles (2 lm) were treated with 0.5 M NaCl or CaCl 2 solution to convert the kaolinite to the sodium form (Na-or Ca-kaolinite). The cation exchange capacity (CEC) of Na-kaolinite was determined by using ammonium acetate (1 M) as described by Black and Hannah (1961). The cation content was determined by atomic absorption spectrophotometer, Shimadzu Corporation, AA-6701/6601 Series.…”
Section: Clay Separation and Saturationmentioning
confidence: 99%
“…Mattson 8 in 1928 reported on his extensive electrophoresis studies of clays and concluded that the hydrolysis products of aluminum and iron are primarily responsible for the neutralization and coagulation of electronegative colloids. He further stated that these hydrolyzed species are more effective than the three-plus ion itself.…”
Section: Hydrolyzing Metalsmentioning
confidence: 99%
“…As described by Peterson and Bartow, 1 and again by Black, Rice, and Bartow," sulfate has the effect of broadening the pH range of coagulation to the acid side. In a previous study, the present authors 8 investigated the coagulation of the Gram negative bacterium Escherichia coli by aluminum nitrate. Changes in turbidity during settling were used as an indication of aggregation and the entire aluminum nitrate concentration-pH "domain of stability" for the coagulation of the organisms was established.…”
mentioning
confidence: 99%
“…Although electrophoretic mobility was recognized by Reuss in 1809, it was not related to water or water treatment before 1928, when Mattson published his ground-breaking study.' Even then, it was not until Black [2][3][4][5][6] and associates published a series of papers beginning in 1958 that ZP in water treatment received the attention it deserved.…”
Section: Zeta Potentialmentioning
confidence: 99%